The Effectiveness of Mindfulness-Based Cognitive Therapy on Quality of Life and Resilience in Women with Chronic Pain - Pouryounes Abkenar, Reza; Ebrahimi Looyeh, Mozhgan; Shamsaldini, Ahmad (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The present study aimed to examine the effectiveness of mindfulness-based cognitive therapy on the quality of life and resilience of women suffering from chronic pain.Method: This was a quasi-experimental study using a pre-test, post-test, and follow-up design with a control group. The sample consisted of 120 women with chronic pain who visited medical centers in Tonekabon, from which 30 were selected through simple random sampling and randomly assigned to either the experimental group or the control group (15 per group). Data were collected using the Quality of Life Questionnaire (Ware & Sherbourne, 1992) and the Connor-Davidson Resilience Scale (2003). The experimental group received eight weekly sessions based on the Kabat-Zinn protocol (2003). During this period, the control group did not receive any training. Data were analyzed using repeated measures and SPSS software version 22.Findings: The results indicated that mindfulness-based cognitive therapy significantly improved the quality of life (F=15.25, p